Analysis of the Downstreaming Policy and Factors Affecting Indonesia’s Nickel Export Performance (HS 75), 2010–2023 - Mochamad Rizal Anwar; M. Taufiq (International Journal of Economics, Commerce, and Management, 2026)
Nickel has become a strategic mineral in the global industrial value chain, particularly for stainless steel production and electric vehicle battery manufacturing. As one of the world’s largest nickel producers, Indonesia has implemented a downstream industrialization policy aimed at increasing value added and strengthening export performance. This study analyzes the effects of international nickel prices, destination countries’ GDP per capita, exchange rates, and the downstreaming policy on the value of Indonesia’s nickel exports (HS 75) over the period 2010–2023. The study employs a quantitative approach using panel data regression with secondary data covering five major export destination countries, namely China, Japan, South Korea, Thailand, and Singapore. Based on the Chow and Hausman tests, the Fixed Effects Model is selected as the most appropriate estimation technique, indicating the presence of country-specific heterogeneity among importing countries. The results show that destination countries’ GDP per capita and international nickel prices have a positive and statistically significant effect on Indonesia’s nickel export value. The downstreaming policy dummy variable also exhibits a positive and significant impact, suggesting that the nickel ore export ban implemented since 2020 has effectively shifted export composition toward higher value-added processed nickel products. In contrast, exchange rates are found to have no significant effect on export performance. Overall, the findings provide empirical evidence supporting the effectiveness of Indonesia’s downstream industrialization policy and highlight the importance of global demand conditions in driving the performance of processed nickel exports.